2006
DOI: 10.1016/j.cub.2006.08.090
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/Frizzled Signaling Controls C. elegans Gastrulation by Activating Actomyosin Contractility

Abstract: We conclude that Wnt signaling regulates C. elegans gastrulation through regulatory myosin light-chain phosphorylation, which results in the contraction of the apical surface of ingressing cells. These findings forge new links between cell-fate specification and morphogenesis, and they represent a novel mechanism by which Wnt signaling can regulate morphogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
165
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(171 citation statements)
references
References 56 publications
6
165
0
Order By: Relevance
“…4B, left and Table S2). Previous work has demonstrated the importance of Wnt signaling in regulating actomyosin contractility (37). Furthermore, high levels of the noncanonical Wnt downstream effector ROCK has been shown to trigger osteogenesis through a myosin-generated tension feedback loop (23,38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B, left and Table S2). Previous work has demonstrated the importance of Wnt signaling in regulating actomyosin contractility (37). Furthermore, high levels of the noncanonical Wnt downstream effector ROCK has been shown to trigger osteogenesis through a myosin-generated tension feedback loop (23,38).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also shown how Wnts are activated by mechanical stimuli during bone development (43,44) with additional functions in regulating cell contractility during tissue morphogenesis (37,45). p38, ERK, and JNK cascades are known to be activated by mechanical stimuli but have also been implicated as targets of Wnt signaling through canonical (40) and noncanonical pathways (41,46,47) for regulation of osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…NM IIB is the subtype most frequently reported to mediate directional cell migration in vertebrates (17,39). In several cases canonical Wnt signaling lies upstream of NM II (40)(41)(42). In feather buds, anterior dermal cells (NM IIB-) remain relatively stationary whereas the posterior dermal cells (NM IIB+) exhibit polarized movements.…”
Section: Discussionmentioning
confidence: 99%
“…Following A/P polarization, chiral cortical actomyosin activity patterns the D/V and L/R axes [187,188,191,192,197] (see above), and cortical contractility drives cell internalization and most likely also cell sorting during gastrulation [197,[262][263][264][265][266][267]. The central inductive cue(s) that drives non-muscle myosin II activation during gastrulation is constituted by Wnt signaling [200,265].…”
Section: Actomyosinmentioning
confidence: 99%
“…The central inductive cue(s) that drives non-muscle myosin II activation during gastrulation is constituted by Wnt signaling [200,265]. This function of Wnt seems to be conserved during later development [268] and among animals: Wnt signaling can cell-autonomously modulate actomyosin distribution, activity, and apical-basal polarization [269,270], and Wnt/planar cell polarity pathway components also seem to directly modulate actin dynamics [271].…”
Section: Actomyosinmentioning
confidence: 99%